USE OF GEOMETRIC PATTERNS AND THEIR TYPES FROM ELIMINATIONS OF DRAWING AND APPLIED ART IN ARCHITECTURAL FACILITIES - Toshpulatov, Faxriddin (Физико-технологического образование, 2022)
The article presents theoretical information about the development of aesthetic culture and spatial imagination of students using elements of drawing and applied art, as well as elements of geometric patterns in our historical architecture